Effects of botanical drugs in the treatment of cancer-related fatigue in patients with gastric cancer: A meta-analysis and prediction of potential pharmacological mechanisms - Wang, Ziming; Wu, Zihong; Xiang, Qiong; Yang, Jingyi; Xia, Zhenzhong; Hao, Aohan; Song, Enfeng; Mei, Shasha (Frontiers in Pharmacology, 2022)
Objective: To systematically review the efficacy and safety of botanical drugs in the treatment of cancer-related fatigue (CRF) caused by gastric cancer (GC) and to determine the underlying pharmacological mechanisms using a network analysis Methods: Databases such as China National Knowledge Infrastructure (CNKI), SinoMed, Wanfang, Pubmed, Embase, Cochrane Library, and Web of Science were searched for randomized controlled trials (RCTs) from inception to April 18, 2022. Methodological quality assessment was performed using the collaborative tool Cochrane, and data analysis were carried out using RevMan 5.4 and STATA 16 software. The botanical drugs with the highest frequency of use in the included studies was selected. The chemical composition, targets of action, disease targets, and shared targets of these botanical drugs were screened based on network analysis to explore the potential mechanisms of treating CRF in patients with gastric cancer (GC). Results: A total of 13 studies that included 986 patients with gastric CRF met the inclusion criteria. The results showed that botanical drugs could improve the CRF scores of gastric CRF, including the total scores of CRF dichotomous data, the total scores of CRF continuous data , the affective subscales of Piper Fatigue Scale (PFS) scores, the sensory subscales of PFS scores , the behavioral subscales of PFS scores, Quality of Life Questionnaire Core 30 (QLQ-C30) , and the Karnofsky Performance Status scale (KPS) . The botanical drugs group had milder adverse effects than the control group. A total of 44 chemical components and 241 potential targets were obtained from the online database and 121 drug targets overlapped with the disease targets of CRF in patients with GC. Moreover, five key active ingredients, namely quercetin, Stigmasterol, luteolin, kaempferol, as well as five key targets including AKT1, TP53, TNF, VEGFA, and CASP3, were screened. In addition, five key signaling pathwayswere obtained through enrichment analysis. Conclusion: The results of the study showed that botanical drugs have positive effects on CRF in patients with GC. However, more well-designed, multicenter, and large sample-sized Randomized Controlled Trials are required to evaluate the effectiveness of botanical drugs on CRF in patients with GC.